Bonjour
On considère l'expression : C = ( 2 x - 5 )² - ( 2 x - 5 )( 3 x - 7 )
a) Développer et réduire C.
C = ( 2 x - 5 )² - ( 2 x - 5 )( 3 x - 7 )
C = 4x² - 20x + 25 - (6x² - 14x - 15x + 35)
C = 4x² - 20x + 25 - 6x² + 14x + 15x - 35
C = 4x² - 6x² - 20x + 14x + 15x + 25 - 35
C = - 2x² + 9x - 10
b) Factoriser l'expression C.
C = ( 2 x - 5 )² - ( 2 x - 5 )( 3 x - 7 )
C = (2x - 5) [(2x - 5) - (3x - 7)]
C = (2x - 5) (2x - 5 - 3x + 7)
C = (2x - 5) (- x + 2).
c) Résoudre l'équation :
(2 x - 5 )( 2 - x ) = 0
2x - 5 = 0 ou 2 - x = 0
2x = 5 - x = - 2
x = 5/2 x = 2.